The Importance of Halal Certificates in Halal Food Using the Digital Platform - Nurillah, Shinta Lintang (Nursyam Centre, 2023)
The world's fast progress, particularly in the realm of technology, necessitates the adaptation of diverse sectors to current developments. The COVID-19 epidemic has had a minimal influence on communal activities as a result of the Indonesian government's strategy of imposing large-scale social restrictions. Restrictions have an influence not just on the major company sector, but also on the small and medium enterprise (MSME) sector. The COVID-19 epidemic has become a new issue for MSMEs in the midst of business innovation rivalry and the need to think of other solutions to continue selling, even if only from home. The fast evolution of digital technology is the outcome of efforts to fulfill human life's requirements. The basic essentials of existence are food. According to Article 29 of the Republic of Indonesia's 1945 Constitution,